Anti-social behaviour in Northern Ireland - Sturgeon, Brendan (Cambridge Scholars Pub., 2011)
Anti-social behaviour has rapidly emerged as one of the most pressing concerns facing the UK. There are frequent media reports on the issue. Many academics and policy makers have also attempted to define the term and analyze why such disorder happens. The research has been extremely valuable, but few studies have specifically analyzed the issue of anti-social behaviour in Northern Ireland. This book seeks to fill this gap in knowledge. This study considers whether certain aspects of the Trou ...